The Zabaleen of Egypt: citizenship of exception in Cairo's urban sphere - Vallis, Kathryn (AUC Knowledge Fountain, 2020)
This thesis examines the relationships between citizenship, space, and the state, using the Zabaleen community in Cairo as a lens of analysis. The thesis argues that citizenship is both an institution and a practice of exclusion. It explores the social, political, and economic exclusions that the Zabaleen experience due to their position in a state of exception.